Pharmacokinetics and Tissue Distribution in Rats After Oral Administration of Tibetan Medicine Wuwei Leze Powder - Ping Wang; Peng Wang; YiRui Wu; ShuiYing Wu; HuiJuan Xu; WenYu Yang; Ya Tu; Chuan Liu (Chemistry & Biodiversity, 2026)
ABSTRACT Wuwei Leze Powder (WLP, སླྱེ་ཏྱེསལྔ་ཐང།) is a classic Tibetan medicine formula with clinical efficacy against rheumatoid arthritis (RA), but its in vivo pharmacokinetic (PK) behavior is unclear. This study aimed to elucidate the absorption, metabolism, pharmacokinetics, and tissue distribution of WLP in rats. UPLC‐Q‐TOF‐MS and UPLC‐QQQ‐MS were used to qualitatively and quantitatively analyze WLP components in rat plasma and tissues. Fifty‐six plasma constituents (21 prototypes, 35 metabolites) were identified. Nine compounds—syringin, cordifolioside A, sweroside, mangiferin, norswertianolin, isovitexin, ellagic acid, amarogentin, and arjungenin—were quantified. All were detectable in plasma within 15 min, with peak concentrations at 0.75–2 h ellagic acid and mangiferin showed the highest systemic exposure ( AUC 0→t : 5007.26 and 3354.21 µg/L·h; C max : 1491.27 and 749.00 µg/L). Half‐lives ranged from 2.63 to 5.26 h. All nine compounds distributed to all tested tissues within 0.5 h, with residues significantly decreased by 8 h and no accumulation observed. The nine compounds are rapidly absorbed and broadly distributed, particularly to synovium, liver, and kidney. Amarogentin, mangiferin, ellagic acid, cordifolioside A, and arjungenin are identified as primary in vivo exposed compounds, supporting the potential pharmacodynamic material basis of WLP against RA.